Giordano Bruno and Bonaventura Cavalieri's theories of indivisibles: a case of shared knowledge. Issue 4 (2nd October 2018) - Rossini, Paolo
ABSTRACT: At the turn of the seventeenth century, Bruno and Cavalieri independently developed two theories, central to which was the concept of the geometrical indivisible. The introduction of indivisibles had significant implications for geometry – especially in the case of Cavalieri, for whom indivisibles provided a forerunner of the calculus. But how did this event occur? What can we learn from the fact that two theories of indivisibles arose at about the same time? These are the questions addressed in this paper. Relying on the methodology of "historical epistemology", this paper asserts that the similarities and differences between the theories of Bruno and Cavalieri can be explained in terms of "shared knowledge". The paper shows that the idea – on which both Bruno and Cavalieri build – that geometrical objects are generated by motion was part of the mathematical culture of the time. Tracing this idea back to its Pythagorean origins thus sheds light on the relationship between motion and continuum in mathematics.